(untitled) (Journal of Parents and Teachers, 2012)
In this article, the author explains why maths are such a problem in the spanish educational system. Also, he tries to explain with questions and answers that maths are not only important because of the competencies related to numbers that the students learn but because maths can be applied in all aspects of life.